Assessment of impaired coordination between respiration and deglutition in children and young adults with ataxia telangiectasia. (23rd May 2016) - Lefton‐Greif, Maureen A; Perlman, Adrienne L; He, Xuming; Lederman, Howard M; Crawford, Thomas O
Abstract : Aim: This cross‐sectional investigation aimed to assess the value of non‐invasive measures of temporal respiratory–swallow coupling in individuals with ataxic swallowing. Method: Twenty participants (11 males, 9 females; range 9‐21y) with ataxia telangiectasia were presented with water and pudding boluses. Their 193 swallows were compared with 2200 swallows from 82 age‐matched healthy controls. The two components of airway protection during swallowing that were analyzed were: direction of peri‐deglutitive airflow and duration of deglutitive inhibition of respiratory airflow (DIORA). Results: Safe expiratory patterns of peri‐deglutitive airflow occurred significantly less often in participants with ataxia telangiectasia than in age‐matched control participants (younger p <0.015 and older p <0.001). The frequency of an expiratory pattern of peri‐deglutitive airflow increased with age in participants in the comparison group ( p =0.006), but not in those with ataxia telangiectasia ( p =0.234). With age, mean duration of DIORA decreased in controls ( p <0.001) but was unchanged in participants with ataxia telangiectasia ( p =0.164). Interpretation: Non‐invasive quantitative measures of respiratory–swallow coupling capture temporal relationships that plausibly contribute to airway compromise from dysphagia. Changes in respiratory–swallow coupling observed with advancing age in control participants were not seen in participants with ataxia telangiectasia. Measures of perturbations may herald swallowing problems prior to development of pulmonary and nutritional sequelae. What this paper adds: Non‐invasive technologies can quantify respiratory–swallow coordination associated with progressive ataxia. Ataxic dysphagia is characterized by aberrant respiratory–swallow coupling. This aberrant coupling is associated with increased risk of aspiration. Perturbations in respiratory–swallow coupling may signify impaired development and/or neurodegeneration. This article is commented on by Capra on pages999–1000 of this issue.